2018
DOI: 10.1111/1462-2920.14332
|View full text |Cite
|
Sign up to set email alerts
|

2,3‐Butanediol catabolism in Pseudomonas aeruginosa PAO1

Abstract: 2,3-Butanediol (2,3-BD) is a primary microbial metabolite that enhances the virulence of Pseudomonas aeruginosa and alters the lung microbiome. 2,3-BD exists in three stereoisomeric forms: (2R,3R)-2,3-BD, meso-2,3-BD and (2S,3S)-2,3-BD. In this study, we investigated whether and how P. aeruginosa PAO1 utilizes these 2,3-BD stereoisomers and showed that all three stereoisomers were transformed into acetoin by (2R,3R)-2,3-butanediol dehydrogenase (BDH) or (2S,3S)-2,3-BDH. Acetoin was cleaved to form acetyl-CoA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Likely, the answer lies in the lifestyle carried out by the microorganism at this condition. In this context, and as mentioned before, it has been shown that utilization of BD, a common fermentation product of P. aeruginosa co-habitant bacteria, significantly increases virulence and infection of the microorganism (Venkataraman et al, 2014; Nguyen et al, 2016; Liu et al, 2018). The activation of the pathway of BD utilization through acetoin by light observed could plausibly go in this same sense too in A. baumannii .…”
Section: Discussionmentioning
confidence: 54%
“…Likely, the answer lies in the lifestyle carried out by the microorganism at this condition. In this context, and as mentioned before, it has been shown that utilization of BD, a common fermentation product of P. aeruginosa co-habitant bacteria, significantly increases virulence and infection of the microorganism (Venkataraman et al, 2014; Nguyen et al, 2016; Liu et al, 2018). The activation of the pathway of BD utilization through acetoin by light observed could plausibly go in this same sense too in A. baumannii .…”
Section: Discussionmentioning
confidence: 54%
“…The effector of the 2,3-butanediol operon in P. aeruginosa PAO1 is the metabolic intermediate acetaldehyde (41). Although the effector promiscuity of CsiR may be due to the structural similarity of l -2-HG and glutarate, it is also possible that the response of CsiR to l- 2-HG has a physiological significance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genes involved in the central carbon catabolism and energy metabolism were identified among the upregulated genes in the core biofilm transcriptome. We found acoABCX, involved in the conversion of 2,3-butanediol into aldehydes, 44 to be highly expressed under biofilm conditions as well as the ethanol oxidation genes (exaABDE), which catalyze the conversion of ethanol via acetaldehyde to acetate and subsequently to acetyl-CoA before its introduction into the glyoxylate cycle for further metabolism. 44 Among the downregulated genes were genes involved in the denitrification pathway including genes of the nir, nor, and nos operons.…”
Section: Biofilm Phenotypes Of Clinical P Aeruginosa Isolates Fall Imentioning
confidence: 97%
“…We found acoABCX, involved in the conversion of 2,3-butanediol into aldehydes, 44 to be highly expressed under biofilm conditions as well as the ethanol oxidation genes (exaABDE), which catalyze the conversion of ethanol via acetaldehyde to acetate and subsequently to acetyl-CoA before its introduction into the glyoxylate cycle for further metabolism. 44 Among the downregulated genes were genes involved in the denitrification pathway including genes of the nir, nor, and nos operons. Furthermore, genes of the arginine succinyltransferase (AST) pathway (aruBG encoding the AST; astD and argD) required for aerobic arginine catabolism were commonly downregulated.…”
Section: Biofilm Phenotypes Of Clinical P Aeruginosa Isolates Fall Imentioning
confidence: 97%